Daily 800 mg versus 600 mg Efavirenz for HIV Patients Treating Tuberculosis with a Rifampicin-Based Regimen: An Open Label Randomized Controlled Trial. - Xavier, Mariana S.; Trajman, Anete; Schmaltz, Carolina A. S.; Sant'anna, Flavia M.; Maia, Ivan R.; Hadad, David J.; Brasil, Pedro Emmanuel A. A. do; Rolla, Valeria (BioMed Research International, 2018)
Objectives. Pharmacokinetics studies recommend increasing efavirenz dosage in tuberculosis/HIV patients using rifampicin. We aimed to evaluate efficacy and safety of 600 versus 800 mg of efavirenz in tuberculosis/HIV patients using rifampicin. Design. We conducted an open label, multicentre, randomized trial from 2006 to 2012. The primary outcome was the proportion of undetectable viral load (HIV-VL) within six months. Secondary outcomes were time to achieve primary endpoint, trajectories of HIV-VL, proportion of any adverse events (AE), proportion of severe and serious AE (SSAE), and time to treatment interruption due to SSAE. Methods. Efavirenz-naïve patients were randomized 30 days after rifampicin-containing regimens initiation to receive 600 (comparison arm) or 800 mg (intervention arm) efavirenz-based regimens and followed-up for 180 days. Results. Sixty-five and 67 participants were respectively included in the comparison and intervention arms with 64.6% (52.5%-65.1%) and 62.7% (50.7%-73.3%) attaining undetectable HIV-VL in six months. Median time to attain undetectable HIV-VL was 70 days in both arms, with HIV-VL overlapping trajectories during follow-up. Cough, acne, and dizziness were more frequent in the intervention arm. SSAE were observed in 19.1% (13.8%-25.8%) and 25.0% (18.9%-33.2%), respectively. Survival curves up to the first SSAE-attributed treatment interruption were similar. None of the differences were statistically significant. Conclusion. Efficacy of efavirenz was similar regardless of dosage. Differences regarding safety occurred as mild and transient events, which did not interfere with treatment. Similar efficacy and safety (SSAE) and lower tolerance (minor AE) in the intervention group favour the use of 600 mg efavirenz in patients using rifampicin.